Conceptualizing employee’s creativity and innovation for effective leadership / Nabila Huda Ibrahim and Shireen Haron - Ibrahim, Nabila Huda; Haron, Shireen (2014)
Employee’s creativity is fundamental in producing valuable product and innovative service and giving idea to the organization. Creativity results in innovation which both plays role in organizational effectiveness either organizational excellence. In order to gain both creativity and innovation in the organization, effective leadership is an important factor. Study shown the most effective leadership in gaining employee’s creativity and innovation is transformational leadership. The purpose if this study is to analyze and review the latest research on employee’s creativity and innovation. This interpretive review will generate items of measurement for the employee’s creativity and innovation variable in order to measure the level of effective leadership. Ten articles were selected from the year 2010 to 2014 and analyses were done consistently on the research methodology, research questions, hypotheses and findings.